The Effect of Servant Leadership, Human Resource Training and Motivation on Performance Mediated by Job Satisfaction of Employees of the Malinau Regency Education Office, North Kalimantan Province - Gita Ramdhani; Shine Pintor Siolemba Patiro; Taufani Chusnul Kurniatun (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to analyze the factors that influence the performance of employees of the Malinau Regency Education Office with a focus on servant leadership, human resources (HR) training, motivation, and job satisfaction as mediating variables. The study was conducted using a quantitative approach with the Partial Least Square (PLS) method on 66 employees. The results showed that servant leadership has a significant influence on employee performance with a contribution of 61.4%. HR training displays the strongest influence with a coefficient of 0.942, indicating that the quality of training directly improves performance. Motivation made a positive contribution of 25.6% to employee performance. Job satisfaction proved to play an effective role as a mediating variable between servant leadership, HR training, and motivation. The study concluded that a holistic approach through servant leadership, quality training, and a comprehensive motivation system can create a productive work environment. The locality context of Malinau Regency provides a unique perspective in the study of human resource management in a region with specific geographical and socio-cultural characteristics.